TRANSLATION PROCEDURES USED BY THE ENGLISH EDUCATION STUDENTS IN TRANSLATING A CHILDREN STORY - Sulistyoadi Joko Saharjo; Sari, Ni Luh Komang Julyanti Paramita; Trianingrum, Nyoman Nidya (Program Studi Pendidikan Bahasa Indonesia dan Daerah Universitas PGRI Mahadewa Indonesia, 2024)
This research aimed to identify translation procedures which were used by the students of English Education Study Program of Triatma Mulya University in translating children story in form of a legend. This research was a very simple research because it only tried to find out the students translation ability at the begining of joining the translation class. Therefore, the scope of the analysis and data was very simple and limited. The translation procedures proposed by Vinay and Darbelnet (1995) were used to analyze the translation of each phrase that was found in the source language. The research results showed that out of the seven translation procedures, there were four translation procedures which were used by the students, in which, the literal translation procedure was the most dominant procedure (76%). The three other procedures were modulation (10%), equivalence (8%), and transposition (6%).